Development of new Medium Access Control for VANET road safety applications - Lakhdar Kamel OULADDJEDID; Mohamed Bachir YAGOUBI (Université de Laghouat , Bibliothèque centrale, 2021)
The road safety is the main motivation behind inter-vehicular communications under Vehicular Ad-hoc NETwork (VANET). The IEEE 802.11p is the leading standard for VANET which adopted the CSMA as a contention-based MAC technique due to its simplicity, dynamicity, as well as its asynchronicity. However, CSMA is always facing a serious problem called “start-ofinterval contention” where there is a very high probability that several contender transmitting vehicle are located close to each other after switching to the Control Channel (CCH) specially when the network is dense. The collision avoidance mechanism used are not enough to prevent the vehicles from accessing the channel at the same time so that sever transmission collisions will be happening. The CSMA algorithm is so unpredictable, unfair and scales poorly for broadcasted beacons. in the other hand, the Time Division Multiple Access (TDMA) medium access mechanism is an excellent candidate for use in VANETs among existing contention-free MAC techniques. It outperforms CSMA and fulfils the complex communication requirements of the traffic safety applications. However, the price paid for the superior performance of TDMA is the required network synchronization through heavy network control overhead. The focus of this thesis is to investigate the medium access control methods, when used for beaconing protocol over VANET. The first proposal of the thesis is called Carrier Sense for Slotted-ALOHA random multiple access MAC (CSSA MAC). It can be seamlessly integrated on top of the IEEE 802.11p standard. . The second contribution of the thesis is the design of an in-band signalization to enhance the TDMA method. It is called CSma with TDms MAC (CSTD MAC) which aims to ensure a good allocation slots with less network overhead. The conducted simulations show that the proposed schemes give a good performance, in respect to safety application requirements, compared to existing protocols of the same category.